Contínuo e limite entre expressão cristalizada e construção com verbo-suporte à luz do Léxico-Gramática - Picoli, Larissa (Universidade Federal de São Carlos, 2020)
This thesis presents an investigation about the continuum of expressions between frozen idioms and support-verb constructions, and about the limit between these two categories, in 560 sentences formed with the verbs ser, estar, ficar and ter in Brazilian Portuguese, as the expression ser um tiro no pé in the sentence Dar carona é um tiro no pé. This construction seems to be a frozen idiom, because ser um tiro no pé has a non-compositional sense, but it admits the omission of the verb ser, as we can see in the sentence Achei sua atitude um tiro no pé, and this is a property of support-verb constructions. Constructions formed by these verbs are productive in Portuguese, and therefore, relevant to lexicological descriptive studies. Although much recent research on frozen idiom classification has been published, as well as some recent research describing support-verb constructions, many constructions have not been analysed and described yet. In this context, we apply several syntactic operations in sentences constructed or attested on the web with the aim of describing and classifying the syntactic-semantic properties of constructions that are in the limit. Through these properties, we recognize, within the expressions that are in the limit, a set of frozen idioms, and a set of support-verb constructions. The theoretical-methodological model we follow is the Lexicon-Grammar (GROSS, 1975b), which establishes principles of description and systematic classification of predicative elements of languages. This model is based on Zellig Harris' Distributionalism and Transformational Theory (1961; 1964). As a result of the analysis, we propose an elaboration of a language resource in the form of tables of the Lexicon-Grammar, a formalism that allows for easy adaptation to Processing of Natural Language. According to this formalism, it is possible that computer programs, such as Unitex, search and label these constructions in large corpora and, from the results, expand the inventory of initially identified constructions.
Continuum and limit between frozen idioms and support-verb constructions in the light of Lexicon-Grammar
Keywords: Expressão cristalizada; Construção com verbo-suporte; Léxico-Gramática; Frozen idiom; Support-verb construction; Lexicon-grammar; LINGUISTICA, LETRAS E ARTES::LINGUISTICA